IMPROVING STUDENTSâ PRONUNCIATION USING AUDIO VISUAL AIDS (AVAs) AT THE FIFTH YEAR OF AL-AZHAR SYIFA BUDI ELEMENTARY SCHOOL OF SURAKARTA IN ACADEMIC YEAR 2007/2008 (A CLASSROOM ACTION RESEARCH) - Wulandari, Anggar; Laila, Malikatul; Prasetyarini, Aryati (Universitas Muhammadiyah Surakarta, 2008)
The study aims to describe the implementation, result, and studentsâ responses to the implementation of teaching English pronunciation using Audio Visual Aids (AVAs). This descriptive qualitative study requires four procedures: planning, imple- menting, observing, and reflecting. The object of the study is the fifth year consist- ing of 19 students of Al-Azhar Syifa Budi Elementary School of Surakarta. The methods of data collection are pre-test and post-test, interview, questionnaires, and observation. The findings show that the mean score of studentsâ pre-test is 7.5 and the mean score of studentsâ post-test is 9.4. The result of the pre-test and post- test indicates that there is an improvement in studentsâ pronunciation, especially in pronouncing word-stress. The studentsâ responses to the implementation of AVAs are positive. It is proven by their enjoyment and excitement condition during the implementation of AVAs. Besides, their pronunciation ability, especially in pronounc- ing the correct word-stress has also improved. They are very interested in learning English pronunciation by watching video, since they can watch the charactersâ expressions, listen to the native speakerâs voice, and read the subtitling appeared on the screen.Â Key words: AVAs, Classroom Action Research, video, pronunciation, and word-stress.Â